Air conditioners, liquid chilling packages, heat pumps, process chillers and dehumidifiers with electrically driven compressors. Determination of the sound power level. Air conditioners, liquid chilling packages, heat pumps for space heating and cooling, dehumidifiers and process chillers Part 1, (12th September 2022) - British Standards Institution
No abstract available